2019
DOI: 10.1080/00103624.2019.1670836
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Assessments of Stochastic and Deterministic Interpolation Methods in Estimating Soil Attributes Spatial Variability

Abstract: Spatial interpolation methods are frequently used to characterize soil attributes' spatial variability. However, inconclusive results, about the comparative performance of these methods, have been reported in the literature. Therefore, the present study aimed to analyze the efficiency of ordinary kriging (OK) and inverse distance weighting (IDW) methods in estimating the soil penetration resistance (SPR), soil bulk density (SBD), and soil moisture content (SM) using two distinct sampling grids. The soil sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(27 reference statements)
2
6
0
Order By: Relevance
“…However, they did not interpolate sensor-based predictions. Different sampling designs were also compared for mapping various soil properties in References [30,57]. In Reference [30], similar to our study, soil PR, BD, and soil moisture maps derived from a dense grid of 145 samples (20 × 20 m) were more accurate than their corresponding maps derived from a thin grid of 41 samples (40 × 40 m).…”
Section: Baseline Versus Sensor-aided Mapssupporting
confidence: 69%
See 2 more Smart Citations
“…However, they did not interpolate sensor-based predictions. Different sampling designs were also compared for mapping various soil properties in References [30,57]. In Reference [30], similar to our study, soil PR, BD, and soil moisture maps derived from a dense grid of 145 samples (20 × 20 m) were more accurate than their corresponding maps derived from a thin grid of 41 samples (40 × 40 m).…”
Section: Baseline Versus Sensor-aided Mapssupporting
confidence: 69%
“…Different sampling designs were also compared for mapping various soil properties in References [30,57]. In Reference [30], similar to our study, soil PR, BD, and soil moisture maps derived from a dense grid of 145 samples (20 × 20 m) were more accurate than their corresponding maps derived from a thin grid of 41 samples (40 × 40 m). When using the sensor-based prediction on the dense grid for OK, the RMSE of validation improved, indicating more accurate maps.…”
Section: Baseline Versus Sensor-aided Mapssupporting
confidence: 69%
See 1 more Smart Citation
“…The reduction in the number of readings per sample point also caused an increase in the error of the interpolation estimate. Moreover, this behavior was observed by Souza et al (2014) and Nogueira Martins et al (2019), who studied the effect of reducing the density of the sampling grid on spatial variability of soil attributes. As in the present study, Souza et al (2014) found that with the reduction in the number of samples, the relationship between the nugget effect and the plateau (Table 1) gradually diminishes, which characterizes the structure of spatial dependence.…”
Section: Resultsmentioning
confidence: 64%
“…The results show that for ECa, the number of readings per sample point plays a crucial role in obtaining maps with lower uncertainties. Therefore, in studies where the objective is to minimize the uncertainties of the maps generated for ECa, the density of the sampling grid, as reported by Souza et al (2014) and Nogueira Martins et al (2019), and the number of readings per sample point should be considered. Thus, the results indicate that there may be a relationship between sample and subsample densities (number of readings per sampling point) that may influence the elaboration of the maps.…”
Section: Resultsmentioning
confidence: 99%